IDENTIFIKASI GANGGUAN BELAJAR DYSCALCULIA PADA SISWA MADRASAH IBTIDAIYAH - Azhari, Budi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Dyscalculia is a kind of problems facing by many pupils beside of low-level reading skills. In fact, reading and basic arithmetic operation skills are very important in learning other subjects. The purpose of this study was to examine learning problems of dyscalculia students. The subjects of this study were five Madrasah Ibtidaiyah (MI) in Kabupaten Aceh Tamiang. The results showed that dyscalculia students face some difficulties in understanding the concepts or the process of calculation since they find some difficulties in visual processing. Moreover, dyscalculia students also face some difficulties in counting the numbers according to their sequences, memorizing and applying mathematical operations. As the consequence, dyscalculia students face some difficulties in solving even a simple mathematical problem.